Airway management of congenital pulmonary airway malformation resection in neonates and infants: A case cohort study. Issue 8 (27th May 2019) - Narayanasamy, Suryakumar; Adler, Elena; Mahmoud, Mohamed; Burkley, Meghan; Lim, Foong‐Yen; Subramanyam, Rajeev
Abstract: Background: Anesthestic management of congenital pulmonary airway malformation has not been well described in the literature. It is not clear whether one‐lung ventialtion is indicated during thoracoscopic lobectomy and if so, what is the best technique achieve it. Aims: We describe the variables with the two commonly performed surgical techniques, thoracoscopic lobectomy and open thoracotomy, from our institutional database to assess the role of lung isolation and the preferable method of lung isolation technique for congenital pulmonary airway malformation resections. Methods: After institutional review board approval, fetal center records were reviewed retrospectively from January 2010 to July 2016 for patients who underwent congenital pulmonary airway malformation resection. The primary goal was to describe the anesthesia induction‐airway management techniques with emphasis on one‐lung ventilation techniques. Results: Among the 65 resections, one‐lung ventilation was performed in 30 resections (46%) and was primarily achieved by endobronchial intubation in most cases (80%). One‐lung ventilation was performed in a greater number of resections with thoracoscopic lobectomy (96%) compared to open thoracotomies. Conclusion: From our institution cohort, one‐lung ventilation was more commonly used during thoracoscopic resections and was most commonly achieved with endobronchial intubation. Most patients were induced with inhalational anesthesia (sevoflurane), nondepolarizing neuromuscular blocker, and gentle positive pressure ventilation for intubation.